Electrochemically formed α'-NaV2O5: A new sodium intercalation compound. (10th September 2015) - Muller-Bouvet, D.; Baddour-Hadjean, R.; Tanabe, M.; Huynh, L.T.N.; Le, M.L.P.; Pereira-Ramos, J.P.
Highlights: Electrochemical Na intercalation in V2 O5 was investigated at RT, in a 1 M NaClO4 /PC electrolyte. The irreversible formation of NaV2 O5 was induced from the first electrochemical discharge step. Electrochemically formed NaV2 O5 was found isostructural to the high temperature layered α'-NaV2 O5 orthorhombic bronze . Electrochemically formed NaV2 O5 is demonstrated to be a genuine sodium intercalation compound with a high capacity of 120 mAh g −1 available near 1.6 V at C/10 rate and a promising cycling behaviour. Zero strain structural behavior was evidenced from X-ray diffraction and Raman spectroscopy during Na + insertion/extraction in electrochemically formed NaV2 O5 . Abstract: In this work the electrochemical behavior of α-V2 O5 at RT, in a 1 M NaClO4 /PC (propylene carbonate) electrolyte is investigated for the first time. The irreversible formation of a sodiated layered compound is shown from the first electrochemical discharge step. This electrochemically formed compound, with highly stable structure close to that of the high temperature α'-NaV2 O5 orthorhombic bronze, is demonstrated to be a genuine sodium intercalation compound. This material exhibits a high capacity of 120 mAh g −1 available near 1.6 V at C/10 rate with a promising cycling behaviour. X-ray diffraction and Raman spectroscopy show zero strain structural behaviour during Na + insertion/extraction in this large interlayer spacing material.